A Rare Case of Endophthalmitis with Rhizobium radiobacter, Soon after a Resolved Keratitis: Case Report - Andrei Theodor Balasoiu; Ovidiu Mircea Zlatian; Alice Elena Ghenea; Livia Davidescu; Alina Lungu; Andreea Loredana Golli; Anca-Loredana Udriștoiu; Maria Balasoiu (MDPI AG, 2022)
Background: Rhizobium (Agrobacterium) species are plant aerobic bacteria, which in some cases can produce endophthalmitis in humans after corneal trauma. Case presentation: A 42-year-old female patient presented in the Emergency Department of the Emergency County Hospital of Craiova, Romania, reporting pain, epiphora, and blurry vision in her right eye for about five days. This initial infectious keratitis episode was successfully resolved, but after 20 days she presented again after trauma with a leaf with corneal abscess. In the conjunctival secretion, R. radiobacter was identified. Despite antibiotherapy, the patient's state did not improve, and ultimately the eye was eviscerated. Methods: A search was performed in the ProQuest, PubMed, and ScienceDirect databases for the terms Agrobacterium, Rhizobium, radiobacter, and eye. We eliminated non-human studies, editorials and commentaries, and non-relevant content, and excluded the duplicates. Results: In total, 138 studies were initially obtained, and then we selected 26 studies for retrieval. After the selection process, we ended up including 17 studies in our analysis. Most studies reported R. radiobacter endophthalmitis after ocular surgical procedures or outdoor activities that involve exposure to soil. Conclusion: R. radiobacter is a rare cause of endophthalmitis after eye trauma that generally responds well to usual antibiotherapy, but occasionally can evolve to severe, leading to the loss of the eye.